Synthetic, spectroscopic, biological and X-ray crystallographic structural studies on a novel pyridine-nitrogen-bridged dimeric nickel(II) complex of a pentadentate N3S2 ligand - Akbar Ali, Mohammad; Mirza, Aminul Huq; Butcher, Ray J.; Tarafder, M.T.H. (Elsevier Science B.V., 2001)
The Schiff base formed by condensation of 2,6-diacetylpyridine with S-benzyldithiocarbazate (H2SNNNS) behaves as a pentadentate ligand, forming a nickel(II) complex of empirical formula Ni(SNNNS)·H2O that is high-spin with a room-temperature magnetic moment of 2.93 B.M. Spectroscopic data indicate that the ligand coordinates with the nickel(II) ion via the pyridine nitrogen atom, the azomethine nitrogen atom and the thiolate sulfur atom. The crystal and molecular structure of the nickel(II) complex was determined by X-ray crystallography. The complex crystallizes in the monoclinic system, space group C2/c, with a = 15.849(2), b = 18.830(2) and c = 18.447(2) Å and α = 90°, β = 102.179(6)°, γ = 90° and Z = 8. The crystal structure analysis shows that the complex is dinuclear, [Ni(SNNNS)]2·2H2O, in which the nickel(II) ions are bridged by the two pyridine nitrogen atoms of two fully deprotonated ligands. The NiN4S2 coordination geometry about each nickel(II) ion can be described as a distorted octahedron. The Schiff base and its nickel(II) complex were tested against four pathogenic bacteria (Bacillus subtilis, Pseudomonas aeruginosa, methicillin-resistant Staphylococcus and B. subtilis (wild type B29) and pathogenic fungi (Saccharomyces ceciricae, Candida albicans, Candida lypolitica and Aspergillus ochraceous) to assess their antimicrobial properties. Both compounds exhibit mild antibacterial and antifungal activities against these organisms. The anticancer properties of these compounds were also evaluated against Human T-lymphoblastic leukaemia cell lines. The Schiff base exhibits marked cytotoxicity against these cells, but its nickel(II) complex is inactive.